2012
DOI: 10.1007/s13361-012-0490-z
|View full text |Cite
|
Sign up to set email alerts
|

Possible Evidence of Amide Bond Formation Between Sinapinic Acid and Lysine-Containing Bacterial Proteins by Matrix-Assisted Laser Desorption/Ionization (MALDI) at 355 nm

Abstract: We previously reported the apparent formation of matrix adducts of 3,5-dimethoxy-4-hydroxycinnamic acid (sinapinic acid or SA) via covalent attachment to disulfide bond-containing proteins (HdeA, Hde, and YbgS) from bacterial cell lysates ionized by matrix-assisted laser desorption/ionization (MALDI) time-of-flight-time-of-flight tandem mass spectrometry (TOF-TOF-MS/MS) and post-source decay (PSD). We also reported the absence of adduct formation when using α-cyano-4-hydroxycinnamic acid (CHCA) matrix. Further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…Teramoto et al have identified two of a dozen prominent peaks in the spectra of Cutibacterium acnes that are used in subspecies discrimination-a CsbD-like protein and a 7 kD antitoxin [4]-and this is the first report of this kind in bacterial MALDI-TOF spectra. The postsource decay (PSD) effect in the commonly used setting for MALDI-TOF species identification, which includes linear mode with α-cyano-4-hydroxycinnamic acid (HCCA/CHCA) as the matrix, is faint [5,6] and can be ignored as an origin of prominent peaks. Therefore, the ions consisting of such peaks should be proton-added protein molecules without a PSD effect.…”
Section: Introductionmentioning
confidence: 99%
“…Teramoto et al have identified two of a dozen prominent peaks in the spectra of Cutibacterium acnes that are used in subspecies discrimination-a CsbD-like protein and a 7 kD antitoxin [4]-and this is the first report of this kind in bacterial MALDI-TOF spectra. The postsource decay (PSD) effect in the commonly used setting for MALDI-TOF species identification, which includes linear mode with α-cyano-4-hydroxycinnamic acid (HCCA/CHCA) as the matrix, is faint [5,6] and can be ignored as an origin of prominent peaks. Therefore, the ions consisting of such peaks should be proton-added protein molecules without a PSD effect.…”
Section: Introductionmentioning
confidence: 99%
“…The peak at m/z 9955 is a matrix adduct peak of HdeA. [47] The B-subunit of Stx1a is observed at m/z 7695 which is close to its [M+H] + theoretical value of m/z 7691.7. The identity of the peak at m/z 7695 was further confirmed by MS/MS-PSD as shown in Fig.…”
Section: Resultsmentioning
confidence: 61%
“…The peak at m / z 7275 is the bacterial cold shock‐like protein: CspC. The peak at m / z 9955 is a matrix adduct peak of HdeA . The B‐subunit of Stx1a is observed at m / z 7695 which is close to its [M+H] + theoretical value of m / z 7691.7.…”
Section: Resultsmentioning
confidence: 74%
“…The MS/MS spectrum obtained for [I 12 +H] + at m/z 1349.7 (Fig. 2a) exhibited the same four product ion series as described for P2VP (Fig.…”
Section: Ms/ms Characterization Of End-groups In Maldi By-products Ofmentioning
confidence: 53%
“…For example, this approach allowed the number of NH 2 end-groups in synthetic polymers to be determined from mass increments observed in MALDI mass spectra obtained for the so-formed Schiff bases compared to the underivatized original species [9]. In mass spectrometry of peptides, specific reactivity of the MALDI matrix was utilized to decipher the number of targeted amino acid residues from the mass of peptide-matrix covalent adducts, as reported for cysteine with ␣,␤-unsaturated matrices (such as ␣-cyanohydroxycinnamic acid, CHCA) [10,11] or for lysine with sinapinic acid (SA) [12].…”
Section: Introductionmentioning
confidence: 99%